Representasi Kehidupan dalam Cerpen Wangon Jatilawang Karya Ahmad Tohari - Nurhafni Nurhafni (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research is based on the fact that literary works are a reflection of real life. Therefore, this research aims to see the form of representation of life in the short story Wangon Jatilawang by Ahmad Tohari. The method used is descriptive qualitative. The results of the study show that there are four representations of life shown by various characters in the short story Wangon Jatilwang, namely (1) Marginalization, (2) Stereotype, (3) Caring and (4) Religious. Based on the results of the study, it can be concluded that life is inseparable from the bad and good sides. However, as short story lovers, we can learn from the good things.